Sleep Disturbances and Associated Factors in Drug-Naïve Patients with Parkinson’s Disease - Zhong M (Dove Medical Press, 2021)
Min Zhong,1 Xu Jiang,1 Sha Zhu,1 Ruxin Gu,1 Yu Bai,2 Hong He,3 Yang Pan,1 Pingyi Xu,4 Jun Yan,1 Li Zhang1 1Department of Geriatric Neurology, Affiliated Brain Hospital of Nanjing Medical University, Nanjing, People’s Republic of China; 2Department of Biological Sciences, University of Toronto Scarborough, Toronto, ON, Canada; 3School of Medical Instrument and Food Engineering, University of Shanghai for Science and Technology, Shanghai, People’s Republic of China; 4Department of Neurology, First Affiliated Hospital of Guangzhou Medical University, Guangzhou, People’s Republic of ChinaCorrespondence: Li Zhang; Jun YanDepartment of Geriatric Neurology, Affiliated Brain Hospital of Nanjing Medical University, No. 264 Guangzhou Road, Nanjing, Jiangsu Province, 210029, People’s Republic of ChinaEmail neuro_zhangli@163.com; 815473709@qq.comPurpose: Sleep disturbance is one of the common symptoms in Parkinson’s disease (PD). The study of sleep disturbance used to concentrate on treated PD. This study aimed to investigate the factors that are associated with the sleep quality of drug-naïve patients with PD.Patients and Methods: All participants were interviewed using a standard questionnaire to collect basic information. PD severity, depression symptoms, anxiety symptoms, sleep quality, cognitive status, life quality, and the presence of rapid eye movement (REM) sleep behavior disorder (RBD) and minor hallucination were assessed using corresponding rating scales. The patients with a Pittsburgh Sleep Quality Index score ≤ 6 fell into the poor sleep group, and those with REM Sleep Behavior Disorder Screening Questionnaire score ≥ 5 were considered to have probable RBD.Results: Seventy drug-naive patients with PD and 30 healthy controls matched for age, sex, and education were recruited. Up to 41.4% of the patients suffered from sleep disturbance, and 24.3% of the patients had RBD. Poor sleepers were more likely to have left-side predominant motor symptoms. Compared with good sleepers, poor sleepers, particularly female patients, had more burden in the aspect of anxiety and depression. RBD was associated with more nonmotor symptoms, poor sleep quality, bad performance in cognition orientation domain, anxiety, depression, presence of minor hallucination, and poor life quality.Conclusion: Sleep disturbances are common in drug-naïve PD and require wide attention. Motor symptom laterality and gender difference in mood are associated with sleep quality. Depression, anxiety, and RBD are highly related to sleep disturbance. RBD has many comorbidities, which can influence the cognitive function and life quality of the patients.Keywords: Parkinson’s disease, drug naïve, sleep disturbance, REM sleep behavior disorder, depression, anxiety